EU science diplomacy in a contested space of multi-level governance: Ambitions, constraints and options for action - Nicolas Rüffin (Research Policy, 2020)
Science diplomacy recently has gained a remarkable foothold in European policymaking. Both the European Commission and many Member States use the term to label a whole range of issues and activities in their respective policies. This prompts the question what exactly is the current role of the European Commission in the field of external research policies as compared to the Member States traditionally in charge of it. The article draws on the conceptual framework of multi-level governance, in particular the distinction between Type I and Type II governance systems. The aim is to show that the well-established setups for science policy and foreign affairs in the EU at present channel most of the Commission's activities in ways that not run counter to the interests of the Member States. The institutionally set parameters entail a focus on existing programs and activities. However, the Type II character of science diplomacy governance in principle leaves room for changes in jurisdictions and the division of labor, which are subsequently discussed. The paper's argument rests upon the qualitative analysis of expert interviews conducted with representatives from Member States, the Commission, Switzerland, and the US.
Keywords: 330; science diplomacy; foreign policy; science policy; international relations; multi-level governance